PENGARUH PENGGUNAAN FERMENTASI KULIT BUAH KAKAO DALAM KONSENTRAT TERHADAP PERTAMBAHAN BOBOT BADAN DOMBA LOKAL - Nirwana, Nirwana (AgriSains, 2005)
An experiment was done to study the effect of fermented cocoa pod shell flour on body weight, dry matter consumption, and feed efficiency of local sheep. The fermented flour was mixed in concentrate given to the sheep. Details of the feed ration were as follows : i) 0% fermented cocoa pod shell flour (CPSF) in concentrate + maize silage (ad-libitum), ii) 10% fermented CPSF in concentrate + maize silage (ad-libitum), iii) 20% fermented CPSF in concentrate + maize silage (ad-libitum). The was indications that the fermented CPSF concentration gave significant effect on feed efficiency (P=0,01). Higher concentration of fermented CPSF tended to be followed by higher body weight, dry matter consemption and feed efficiency. Key words : Cacao skim flour fermentation, concentrate and feed efficiency.